Implementasi manajemen strategi baznas dalam meningkatkan efektivitas, inovasi digital, dan kepercayaan publik terhadap pengelolaan dana zakat, infak, dan sedekah (zis) - Anggraini, Jesika Devi Mufita (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of strategic management by the National Zakat Agency (BAZNAS) in increasing effectiveness, digital innovation, and public trust in the management of Zakat, Infaq, and Alms (ZIS) funds. This study uses a descriptive qualitative approach by adapting the results of previous research from various regional BAZNAS such as Palembang, Baubau, Parepare, and Bandar Lampung. The results show that BAZNAS’s strategic management is carried out through three main stages: formulation, implementation, and evaluation. Strategy formulation emphasizes the vision of empowering the community and strengthening the digital system. Strategy implementation is carried out through optimizing digital platforms, transparency of financial reports, and the development of technology-based productive programs. Strategy evaluation focuses on increasing public trust through the principles of professionalism, trustworthiness, and accountability. Overall, the implementation of strategic management based on digital innovation plays a significant role in strengthening the effectiveness of ZIS management and increasing community participation.